The Nexus Between Zakat, Population, Scientific and Technical Journal Articles, and Economic Growth: Panel Data Analysis in Muslim-Majority Countries - Lestari, Nurrizka Puji; Syaifullah; Affan, Ibnu; Herianingrum, Sri (Universitas Airlangga, 2024)
ABSTRACT This research aims to analyze the factors that influence the economic growth of a country. This study involves a quantitative investigation using panel data regression in seven mainly muslim nations from 2007 to 2020. The variables used in this research are zakat rate, population, the number of scientific and technical journal articles, and Gross Domestic Product (GDP). This research found that the variables of zakat rate, population, and the scientific and technical journal articles have a partial effect on a country's economic growth. Furthermore, simultaneously, variables such as the zakat rate, population, and the number of scientific and technical journal articles also have a significant effect on economic growth. This research also found that zakat rate as the most influential factor in economic growth. First, the government should create effective policies to increase the level of zakat, such as implementing zakat policies as an income tax deduction. This is expected to enhance zakat collection. Second, stakeholders must collaborate to integrate zakat with other policy instruments to create a comprehensive policy framework. Keywords: Economic Growth, Journal Articles, Population, Zakat ABSTRAK Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi pertumbuhan ekonomi suatu negara. Studi ini melibatkan investigasi kuantitatif menggunakan regresi data panel di tujuh negara mayoritas muslim dari tahun 2007 hingga 2020. Variabel yang digunakan dalam penelitian ini adalah tingkat zakat, populasi, jumlah artikel jurnal ilmiah dan teknis, dan Produk Domestik Bruto (PDB). Penelitian ini menemukan bahwa variabel tingkat zakat, populasi, dan artikel jurnal ilmiah dan teknis memiliki pengaruh parsial terhadap pertumbuhan ekonomi suatu negara. Selain itu, secara bersamaan (simultan) variabel tingkat zakat, populasi, dan jumlah artikel jurnal ilmiah dan teknis juga memiliki pengaruh signifikan terhadap pertumbuhan ekonomi. Penelitian ini juga menemukan bahwa tingkat zakat merupakan faktor paling berpengaruh dalam pertumbuhan ekonomi. Penelitian ini memberikan dua rekomendasi. Pertama, pemerintah harus menciptakan kebijakan efektif untuk meningkatkan tingkat zakat, seperti melalui kebijakan zakat sebagai pengurang pajak penghasilan. Ini diharapkan dapat meningkatkan pengumpulan zakat. Kedua, para pemangku kepentingan harus bekerja sama untuk mengintegrasikan zakat dengan instrumen kebijakan lainnya untuk menciptakan kerangka kebijakan yang komprehensif. Kata Kunci: Pertumbuhan ekonomi, Artikel Jurnal, Populasi, Zakat